Avaliação técnica econômica de tilápias cultivadas com diferentes taxas de alimentação em esgoto doméstico tratado - Santos, Emanuel Soares dos (2015)
The research aimed to evaluate technically, through water quality indicators, livestock income and microbiological quality of the produced fish; and economically by means of indicators of economic performance; Nile tilapia Oreochromis niloticus cultivation using different feed rates in treated sewage. Nine (09) tanks with 50 m3 of volume were constructed in concrete and filled with treated sewage, after which were tested three different treatments: WF - depletion of commercial feed; FS 1/2 and FS - feed with 50% and 100% of the supplementation suggested by the supplier, respectively. The zootechnical parameters total length (cm), weight (g), biomass (g/m3), productivity (kg/ha.day) and food conversion rate (CR) were determined. For the economical analysis the following parameters were used: partial operational costs (POC), gross income (GI), partial liquid income (PLI) and cost incidence (CI). Analyses of Salmonella spp., Coagulase-positive staphylococci and coliforms in muscle, skin and gills to verify the quality of the fish produced. The results indicated that treatment FS 1/2 was the best treatment with regard to the technical viability and treatment WF was the best treatment in terms of economical viability. The fish had produced satisfactory sanitary conditions for human consumption.